Approach to Determining the Competitive Position of An Enterprise - Kadyrov T.U (Global Scientific Publishing, 2023)
The article presents a methodological approach to determining the competitive position of modern enterprises in the market, based on the volume of production, cost and sales price of products. Such concepts as analysis of the results of the enterprise, competitive potential, profit, production volume, production cost, average selling price of products are considered. Disclosed are the differences between price and non-price competition, features of a growing, stable and falling market. The effective competitive strategies that ensure the successful functioning of enterprises in various market conditions are considered.
Keywords: competitiveness; competitive position; profit; production volume